Utilization of information and communication technology among undergraduate nursing students in Tanta university, Egypt - Lawal, Umar Bello; Elshafie, IKbal Fathalla; Yunusa, Umar; Ladan, Muhammad Awwal; Suberu, Ahmed; Abdullahi, Saratu G.; Mba, Chioma Judith (CME Publishing Group, 2017)
The use of ICT to enhance learning and teaching has become increasingly important. Information and communication technology in education is a modern, efficient and cost effective process which has created a need to transform how students and teachers from higher institutions learn and teach respectively. This study was conducted to assess the pattern and utilization of Information and Communication Technology among undergraduate Nursing students in Tanta University, Egypt. A descriptive cross sectional design was used for the study where 504 fourth year students enrolled in the 2015/2016 session participated in the study. A validated structured questionnaire was used for data collection. The data collected were analyzed using Statistical Package for Social Science (SPSS) version 20. The results indicated that 80% of the surveyed students utilized ICT in performing their study assignments and research. Majority of the female students (79.0%) self reported themselves as good in computer skills while only one fifth (21.0%) of the male students rated themselves as good in computer skills. Students whose parents had secondary education and above had their total score in self-rating of computer operation skills as significantly higher than those whose parents had below secondary education. The study concluded that majority of the students had good ICT utilization with variation to residence and family income. It is therefore recommended that the university should ensure strict compliance with the rules of e-learning courses for the students and ensure proper application by each student.